2018
DOI: 10.3390/su10061931
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Sensitivity of Multi-Species Afforestation in Semi-Arid Benin

Abstract: Abstract:The early growth stage is critical in the response of trees to climate change and variability. It is not clear, however, what climate metrics are best to define the early-growth sensitivity in assessing adaptation strategies of young forests to climate change. Using a combination of field experiments and modelling, we assessed the climate sensitivity of two promising afforestation species, Jatropha curcas L. and Moringa oleifera Lam., by analyzing their predicted climate-growth relationships in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…An 'ensemble habitat suitability' can be calculated as the weighted average of suitability estimates predicted by different algorithms (Kindt 2018). Analysis by Noulèkoun et al (2018) suggested that the climate parameters for predicting tree growth in the year of establishment (longest dry spell in rainy season) differ from those for the subsequent growth of trees with established root systems (overall balance of potential evapotranspiration and rainfall). There is also literature describing the way tree distribution and dynamics respond to rainfall trends over periods of several years and the interactions of these with human activity (Maranz 2009;Mbow et al 2015;Brandt et al 2016Brandt et al , 2017.…”
Section: Current State Of the Artmentioning
confidence: 99%
“…An 'ensemble habitat suitability' can be calculated as the weighted average of suitability estimates predicted by different algorithms (Kindt 2018). Analysis by Noulèkoun et al (2018) suggested that the climate parameters for predicting tree growth in the year of establishment (longest dry spell in rainy season) differ from those for the subsequent growth of trees with established root systems (overall balance of potential evapotranspiration and rainfall). There is also literature describing the way tree distribution and dynamics respond to rainfall trends over periods of several years and the interactions of these with human activity (Maranz 2009;Mbow et al 2015;Brandt et al 2016Brandt et al , 2017.…”
Section: Current State Of the Artmentioning
confidence: 99%
“…Not surprising, recent research in Benin [40] is finding, "a multi-species afforestation system with species that are able to develop deep-penetrating root systems may increase the resilience of plantations to climate change" -which is suggested as an answer to "projected increase in variability of precipitation distribution, extended arid conditions, and longer dry spells in West Africa". Investigation of root growth of different tree species showed the "importance of root depth in buffering the negative effects of extreme drought on sapling".…”
Section: Choice Of Authochtone and Ecologically Adapted Species Natur...mentioning
confidence: 99%
“…Agroforestry reduces soil and water erosion, improves water management, and reduces crop yield variability, all of which contribute to adaptation (Ajayi et al, 2007(Ajayi et al, , 2009Franzel, 2002;Mercer, 2004). According to Noulèkoun et al (2018), the climate parameters for predicting tree growth in the year of establishment (longest dry spell in rainy season) is different from those for the subsequent growth of trees with the established root system, i.e. overall balance of potential evapotranspiration and rainfall.…”
Section: Introductionmentioning
confidence: 99%